Perubahan Identitas Tokoh Light Yagami Sebagai ‘Kira’ Dalam Anime Death Note Menurut Psikoanalisis Lacanian - Ahmad Fadhil Aulia Arif; Sri Oemiati (KIRYOKU, 2026)
This study aims to describe the identity transformation of Light Yagami as Kira in the anime Death Note by Tsugumi Ohba. Using a qualitative descriptive method, the research focuses on understanding the character and the context surrounding his psychological development. Death Note was chosen as the primary data source because Light demonstrates a drastic shift in identity—from an intelligent high school student to a murderer who justifies his actions in the name of justice. Lacan’s psychoanalytic theory is employed to examine this transformation, as it highlights the relationship between desire, lack, language, and the law. The findings show that Light’s development corresponds to three Lacanian stages: the mirror stage, the symbolic order, and the real. In the mirror stage, Light constructs an ideal image of himself as a bringer of justice. His inherent human lack then generates a desire to become a perfect, god like figure. Within the symbolic order, this desire materializes through the Death Note, which functions as a symbol of absolute authority over moral law. In the stage of the real, Light becomes trapped in a destructive form of jouissance that ultimately consumes his humanity. Altogether, these stages reveal that Kira is a constructed illusion Light creates to mask his fundamental human limitations.